A case of acute onset postoperative gas gangrene caused by Clostridium perfringens. (December 2016) - Takazawa, Tomonori; Ohta, Jou; Horiuchi, Tatsuo; Hinohara, Hiroshi; Kunimoto, Fumio; Saito, Shigeru
Abstract Background Gas gangrene is a necrotic infection of soft tissue associated with high mortality rates. We report a case of postoperative gas gangrene with very acute onset and rapid progression of symptoms. To our knowledge, this case is the most acute onset of postoperative gas gangrene ever reported. Case presentation A 65-year-old Japanese female patient developed a shock state 16 h after radical cystectomy with ileal conduit reconstruction. Two days after the operation, she was transferred to the intensive care unit because of deterioration in her respiratory and circulatory condition. Soon after moving her to the ICU, a subcutaneous hemorrhage-like skin rash appeared and extended rapidly over her left side. Blood tests performed on admission to the ICU indicated severe metabolic acidosis, liver and renal dysfunction, and signs of disseminated intravascular coagulation. Suspecting necrotizing fasciitis or gas gangrene, we performed emergency fasciotomy. Subsequently, multidisciplinary treatment, including empirical therapy using multiple antibiotics, mechanical ventilation, hyperbaric oxygen therapy, polymyxin B-immobilized fiber column direct hemoperfusion, and continuous hemodiafiltration, was commenced. Culture of the debris from a wound abscess removed by emergency fasciotomy detected the presence ofClostridium perfringens . We hypothesized that the source of infection in this case may have been the ileum used for bladder reconstruction. Although the initial treatment prevented further clinical deterioration, she developed secondary infection from the 3rd week onward, due to infection with multiple pathogenic bacteria. Despite prompt diagnosis and intensive therapy, the patient died 38 days after the operation. Conclusion Although the patient did not have any specific risk factors for postsurgical infection, she developed a shock state only 16 h after surgery due to gas gangrene. Our experience highlights the fact that physicians should be aware that any patient could possibly develop gas gangrene postoperatively.